Charles Darwin and Ethics: From Sociability to Morality - Velázquez Jordana, José Luis (Estudios de Filosofía, 2010)
Charles Darwin´s most important contribution to Moral Philosophy is an explanation of the origin and development of the moral condition of the human being exclusively from the perspective of Natural History. Starting with the publication of The Descent of Man, in 1871, this statement has aroused strong controversies, to the point of becoming a criterion with which to distinguish the traditional conceptions of Morality from the modern conceptions of Morality. This essay is an articulated description of the structure of Morality according to Charles Darwin, considering three aspects of Moral Conscience: The evolutionary origin and the evolutionary stages of its development, the emotional or sentimental basis of Morality with special attention to the feeling of Sympathy, and the normative dimension inspired by Kantian and Utilitarian traditions. The main conclusion established here is that the sociability of human beings is a necessary but not sufficient condition of Morality. In addition to this, some difficulties found in the statement of Darwin when he tried to reconcile the two moral traditions mentioned are gathered.